Laparoscopic Implantation of Distal Peritoneal Ventriculoperitoneal Shunt Catheter: A Comparative Study - Cohen-Inbar, Or; Krausz, Michael; Zaaroor, Menashe; Mahajna, Ahmad (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Objective Ventriculoperitoneal shunts (VPS) are a common treatment for hydrocephalus. Placement of the distal abdominal catheter can be difficult in the setting of advanced age, previous abdominal surgeries, obesity, or chronic illnesses. At our institute, complex patients are treated using a multidisciplinary team of a neurosurgeon and a laparoscopic surgeon. We evaluated the influence on prognosis of a laparoscopically assisted VPS placement using a single-port technique as compared with the conventional mini-laparotomy approach.Methods Between 2006 and 2010, 302 patients were operated for hydrocephalus or shunt dysfunction. Among these, a total of 48 patients were operated on using the single-trocar laparoscopy. Neurosurgeons and laparoscopic surgeons logged the presenting symptoms, past medical history, chronic diseases, past surgical procedures, the actual surgical procedure and intraoperative findings. Outcome data were collected at several time points, using several independent outcome parameters.Results The laparoscopic group was significantly older, had more chronic diseases, and had more prior abdominal and shunt operations. However, this group had the same outcome as the minilaparotomy group..Conclusions The outcome of elderly patients, patients with chronic diseases and obesity, and patients who underwent previous abdominal or shunt operations equals the outcome of young, otherwise healthy patients, if the laparoscopic single-port technique for distal catheter placement during VPS procedure is used. The laparoscopic technique reduces surgical complications.
Keywords: single-trocar technique; laparoscopic aided neurosurgery; ventriculo-abdominal shunt